Classpects: unifying aspect- and object-oriented language design - Rajan, Hridesh; Sullivan, Kevin J. (Proceedings of the 27th international conference on Software engineering, 2005)
The contribution of this work is the design, implementation, and early evaluation of a programming language that unifies classes and aspects. We call our new module construct the classpect. We make three basic claims. First, we can realize a unified design without significantly compromising the expressiveness of current aspect languages. Second, such a design improves the conceptual integrity of the programming model. Third, it significantly improves the compositionality of aspect modules, expanding the program design space from the two-layered model of AspectJ-like languages to include hierarchical structures. To support these claims, we present the design and implementation of Eos-U, an AspectJ-like language based on C# that supports classpects as the basic unit of modularity. We show that Eos-U supports layered designs in which classpects separate integration concerns flexibly at multiple levels of composition. The underpinnings of our design include support for aspect instantiation under program control, instance-level advising, advising as a general alternative to object-oriented method invocation and overriding, and the provision of a separate join-point-method binding construct.